Time budgets of Mandarin Ducks under semi-natural conditions - Bruggers, Richard L; Jackson, William B (Wildfowl, 1977)
The daily activity patterns of free-ranging pinioned Mandarin Duck Aix galericulata consisted of repetitious feeding, preening, and loafing with variations related to the different social periods. Diurnal activity rhythms were obvious only during the summer and fall when the birds fed and preened during the morning and late afternoon and loafed the rest of the day. Renesting time budgets were different from those on the initial nesting period, the females preened more and fed less. Females spent 8 hours/day feeding (primarily surface feeding); their mates, considerably less. These instead remained alert, presumably reducing harassment to the female by other males and allowing her to feed extensively. During incubation females were on the nest 80% of the day and all night. They generally had pre-dawn and dusk periods of the nest each day. Males threatened conspecifics and waited for their incubating females at loafing spots (often in view of the nest) throughout incubation and attended them when they were off the nest, when the females fed 90% of the time, preened, and bathed. Mandarins surface-fed, grazed, tipped-up, and caught fish and flying insects. The general feeding patterns changed during the day (swim-feeding in the morning and grazing in the evening) and during the season (from nearly exclusive surface feeding in pre-laying to only one-third in incubating periods). Preening sessions nearly always followed bathing and feeding. Preening was greatest during the pre-basic and pre-alternate moults and after assuming the alternate plumage. Intense preening during the first two periods undoubtedly was related to irritation of feather replacement; during the latter period, perhaps to pairing. During the summer evening Mandarins entered the lake and swim-fed along the shoreline until 22.00. After feeding they floated alertly, concealed under the over-hanging shoreline vegetation the remainder of the night. One pair, however, continued to feed until 02.00. Night feeding also may occur during the laying and renesting periods.